High prevalence of toxin producing enteropathogenic Vibrios among estuarine crab in Ganges delta of West Bengal, India. - Batabyal, Prasenjit (2014)
Chitin influences the survival of Vibrio spp. in aquatic environment by providing an abundant source of carbon, nitrogen and protection from environmental challenges ( Kirn et al., 2005). Huq et al. (1986) have demonstrated a possible ecological correlation between crustaceans and Vibrio abundance. However, active role of such common edible seafood viz. crabs etc. of aquatic habitat (freshwater/estuarine/marine) as prospective “reservoir” (because of being proven niche of Vibrio cholerae in such environment, Blokesch and Schoolnik, 2007) in cholera and non-cholera diarrhoeal transmission and their possible implications among coastal population of deltaic West Bengal remains unexplored. A few earlier studies have demonstrated the attachment capacity of V. cholerae with chitinous substrate ( Kaneko and Colwell, 1975 and Tarsi and Pruzzo, 1999). This raise queries regarding the extent to which chitin acts in toxicity acquisition under natural environmental condition either being attached with a host specific chitinous substrate or in a free floating condition.